Four Taeniasis saginata Cases Diagnosed at a University Hospital in Korea - Won, Eun Jeong; Shin, Ju Hyeon; Lee, Yu Jeong; Kim, Moon-Ju; Kang, Seung Ji; Jung, Sook In; Kim, Soo Hyun; Shin, Jong Hee; Chai, Jong-Yil; Shin, Sung-Shik (Korean journal of parasitology, 2019)
In recent years, the taeniasis has been rarely reported in the Republic of Korea (Korea). But in this study, we intend to report 4 taeniasis cases caused by Taenia saginata during a 5-month period (February to June 2018) at a unversity hospital in Gwangju, Korea. Worm samples (proglottids) discharged from all cases were identified by phenotypic and molecular diagnostics. Mitochondrial cytochrome c oxidase subunit I sequences showed 99.4-99.9% identity with T. saginata but, differed by 4% from T. asiatica and by 7% from T. multiceps, respectively. We found that tapeworms in 2 cases (Cases 2 and 3) yielded exactly the same sequences between them, which differed from those in Cases 1 and 4, suggesting intra-species variation in tapeworms. These taeniasis cases by T. saginata infection in this study, which occurred within a limited time period and region, suggest the possibility of a mini-outbreak. This study highlights the need for further epidemiological investigation of potentially overlooked cases of T. saginata infection in Korea.